2014
DOI: 10.1002/hbm.22679
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of levodopa‐responsive gait disorders and freezing in advanced Parkinson's disease: A kinesthetic imagery approach

Abstract: Gait disturbances, including freezing of gait, are frequent and disabling symptoms of Parkinson's disease. They often respond poorly to dopaminergic treatments. Although recent studies have shed some light on their neural correlates, their modulation by dopaminergic treatment remains quite unknown. Specifically, the influence of levodopa on the networks involved in motor imagery (MI) of parkinsonian gait has not been directly studied, comparing the off and on medication states in the same patients. We therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 157 publications
(266 reference statements)
7
38
2
1
Order By: Relevance
“…gait) in aging have demonstrated the role of the prefrontal cortex using different neuroimaging methods (Holtzer et al, 2014a) like functional MRI (Allali et al, 2014b; Blumen et al, 2014) or PET-Scan (la Fougere et al, 2010). However, few studies address this issue in older adults with PS using direct online assessments of prefrontal brain regions (Maillet et al, 2014; Thevathasan et al, 2012). In the PS population, extracortical regions, like the pedunculopontine nucleus (Thevathasan et al, 2012) or cerebellar regions (Maillet et al, 2014) appear to play a key role in the cerebral networks involved in the control of gait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gait) in aging have demonstrated the role of the prefrontal cortex using different neuroimaging methods (Holtzer et al, 2014a) like functional MRI (Allali et al, 2014b; Blumen et al, 2014) or PET-Scan (la Fougere et al, 2010). However, few studies address this issue in older adults with PS using direct online assessments of prefrontal brain regions (Maillet et al, 2014; Thevathasan et al, 2012). In the PS population, extracortical regions, like the pedunculopontine nucleus (Thevathasan et al, 2012) or cerebellar regions (Maillet et al, 2014) appear to play a key role in the cerebral networks involved in the control of gait.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies address this issue in older adults with PS using direct online assessments of prefrontal brain regions (Maillet et al, 2014; Thevathasan et al, 2012). In the PS population, extracortical regions, like the pedunculopontine nucleus (Thevathasan et al, 2012) or cerebellar regions (Maillet et al, 2014) appear to play a key role in the cerebral networks involved in the control of gait. In terms of postural control, previous studies (Goble et al, 2011; Karim et al, 2013b) showed that older adults recruit cerebral networks involving temporal and prefrontal regions, as well as the subcortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that PD patients with FOG would be slower and more variable in their step times during the navigation of a turn in the VR 18,19 and that turning would elicit altered activation patterns in the STN 7 and its hyperdirect frontal cortex connections. 9–11 In addition, we expected to find differences across the cortical, striatal and other subcortical regions that have previously been identified in PD patients with FOG during structural MRI, 11,20 fMRI resting state, 21 PET gait imagery tasks 22 and during fMRI with a gait imagery tasks, 23,24 upper limb motor task, 25 and VR performance. 13,16,17 …”
Section: Introductionmentioning
confidence: 97%
“…when the person in the vertical position, rather than in the horizontal position required for concomitant MRI acquisition) ( Bartels and Leenders, 2008;Maillet et al, 2012;Herman et al, 2013;Shine et al, 2013d). Recently, researchers have found new ways of studying FoG by using mental imagery of gait (Snijders et al, 2011;Crémers et al, 2012;Maillet et al, 2015;Peterson et al, 2014aPeterson et al, , 2014b and virtual reality tasks (Shine et al, 2013a(Shine et al, , 2013b(Shine et al, , 2013cShine et al, 2011b). Other functional MRI approaches are based on creating the equivalent of FoG for the upper limbs (Vercruysse et al, 2014a) or performing alternating foot movements in the supine position (Shine et al, 2013a(Shine et al, , 2013b(Shine et al, , 2013cShine et al, 2011b) in order to individualize motor blocks that could be time-locked with changes in brain perfusion.…”
Section: Introductionmentioning
confidence: 99%